2023
DOI: 10.1371/journal.pone.0292012
|View full text |Cite
|
Sign up to set email alerts
|

A wearable-based sports health monitoring system using CNN and LSTM with self-attentions

Tao Yuhuan Wang,
Jiajia Cui,
Yao Fan

Abstract: Sports performance and health monitoring are essential for athletes to maintain peak performance and avoid potential injuries. In this paper, we propose a sports health monitoring system that utilizes wearable devices, cloud computing, and deep learning to monitor the health status of sports persons. The system consists of a wearable device that collects various physiological parameters and a cloud server that contains a deep learning model to predict the sportsperson’s health status. The proposed model combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…LSTM has been widely used to predict events with time series and can be successfully applied. It also outperforms most non-parametric methods [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Related research, including flow forecasts, climate forecasts, and health monitoring, are shown in Table 2.…”
Section: Output Gatementioning
confidence: 99%
“…LSTM has been widely used to predict events with time series and can be successfully applied. It also outperforms most non-parametric methods [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Related research, including flow forecasts, climate forecasts, and health monitoring, are shown in Table 2.…”
Section: Output Gatementioning
confidence: 99%